EDUKASI KESEHATAN TERHADAP PERILAKU MAKAN BAYI DAN BALITA PADA WILAYAH KERJA PUSKESMAS ANAK AIR KOTA PADANG - Ayulia Fardila Sari ZA; Kamal Kasra (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
The prevalence of stunting under five in the working area of the Air Child Health Center in 2020 was 16.3%. This number is the highest compared to all community health centers in Padang City and has not yet reached the national stunting rate target of 14%. The purpose of this activity is to increase the knowledge of mothers in the working area of the Air Child Health Center about the eating behavior of infants and toddlers and to improve the skills of cadres to conduct health education. The community empowerment method used is Emotional Demonstration (Emo-Demo) training on infant and toddler eating behavior, which consists of demonstration, practice, discussion, and question and answer. The activity was carried out on Wednesday, September 29, 2021 at the Jazirah Nur Mosque, Padang City. The training was given to 29 participants, consisting of 4 pregnant women, 16 mothers with toddlers, 8 posyandu cadres, and 1 community Health centers officer. The training materials consist of 4 Emo-Demo modules developed by The Global Alliance for Improved Nutrition (GAIN), namely: 1) infant and child feeding schedule, 2) mother and child bonding, 3) stacking blocks, and 4) random snacks. The result of the activity in general is an increase in mothers' knowledge of the eating behavior of infants and toddlers. This can be seen from the 5 randomly selected participants who were able to correctly answer the questions from the informants. In addition, there was an increase in the skills of posyandu cadres in implementing the Emo-Demo technique. This can be seen from all cadres who are able to practice Emo-Demo without needing to be guided by a facilitator after the training.